(untitled) (Docentes 2.0 Journal, 2025)
English language teaching in early childhood education faces significant challenges in vocabulary learning, primarily due to a lack of motivation and the use of traditional approaches. In this context, this research aimed to analyze the impact of gamification strategies on English vocabulary learning in early childhood education children. A study was conducted within the pragmatic paradigm, with a mixed approach and a narrative-thematic, bibliographic-analytical, and cross-sectional design. Systematic literature review and content analysis techniques were employed for data collection, using a categorical analysis matrix as an instrument. The Scopus database revealed 541 articles published between 2010 and 2025, and fourteen publications were selected based on the PRISMA model. The results showed that gamification strategies, such as interactive games and mobile applications, promote vocabulary retention and increase student engagement in the learning process. However, challenges associated with technological dependence and unequal access to digital resources were identified. The review concludes that gamification, based on constructivist and sociocultural approaches, represents an effective and flexible strategy for enhancing English language learning in early childhood.